1979
DOI: 10.1063/1.438268
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the concept of universal intensities in local mode theory

Abstract: Tetramethylsilane (TMS) Spectra were obtained with a Cary 14-spectropholometer. The intensities in the primary C-H LM overtones and the neighboring sidebands of TMS are given and discussed in terms of the Universal cconcept of intensities. (AIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
4
20
0
Order By: Relevance
“…In spite of the very bright CH fundamental σ u due to the acidic CH bond, their first overtone, to which the latter σ g + σ u mode corresponds, has an intensity insensitive to the CH bond acidity due to the so-called universal intensity concept. 69,70 This phenomenon is a consequence of the intensity cancelation of the firstand second-derivative terms of the DMF with respect to the CH bond displacement, as shown in our previous work. 71 In the NM picture, the large π g + π u combination band intensity is interpreted as a result of the intensity borrowing from the intense CH fundamental σ u due to the third-order anharmonicity (see section 4.3).…”
Section: Resultssupporting
confidence: 73%
“…In spite of the very bright CH fundamental σ u due to the acidic CH bond, their first overtone, to which the latter σ g + σ u mode corresponds, has an intensity insensitive to the CH bond acidity due to the so-called universal intensity concept. 69,70 This phenomenon is a consequence of the intensity cancelation of the firstand second-derivative terms of the DMF with respect to the CH bond displacement, as shown in our previous work. 71 In the NM picture, the large π g + π u combination band intensity is interpreted as a result of the intensity borrowing from the intense CH fundamental σ u due to the third-order anharmonicity (see section 4.3).…”
Section: Resultssupporting
confidence: 73%
“…Takahashi et al 62 calculated the integrated cross sections for the C-H stretching overtones of c-DCE and t-DCE using a local mode model in which both the potential energy surface and the dipole moment function were determined from ab initio calculations. These authors sought to explain the deviation of the t-DCE cross section from the trend observed by Burberry et al 72 of a characteristic ͑molecule-independent͒ integrated cross section per C-H bond for the second through sixth overtones. Finding the vibrational wavefunctions for two DCE isomers to be essentially identical, Takahashi et al 62 explained the experimental discrepancy through a significant difference in the calculated dipole moment functions.…”
Section: ͑3͒mentioning
confidence: 99%
“…ℨ is equal to unity. Using eqs 4 and 5, the molecular and conformational dependence of the absorption intensities can be examined in terms of ρ (1) (r) and ρ (2) (r), including the electric anharmonicity. 32 Molecular electron density at a point r is Taylor expanded around the equilibrium OH bond distance at ΔR = 0 as follows…”
Section: R R R R ( )Dmentioning
confidence: 99%
“…If the time-dependent oscillation is considered through ΔR(t) = A sin ωt, the ρ (1) (r)ΔR and ρ (2) (r)ΔR 2 terms are responsible mostly for the fundamental and overtone absorption intensities, respectively. 46 If ρ (1) (r) and ρ (2) and lower-level overtone intensities will appear with various stereoelectronic effects.…”
Section: R R R R ( )Dmentioning
confidence: 99%
See 1 more Smart Citation